Impact of Strategic Management Accounting Practices on Financial Performance of Nepalese Manufacturing Firms - Ghimire, Keshab (Tribhuvan Journal, 2023)
This study was carried out to examine the relationship between financial performance and the application of management accounting practices in the Nepalese manufacturing firms. The study adopted the survey research design. The population of the study consists of all listed manufacturing companies under Nepal stock exchange. The study used simple random sampling. Four manufacturing firms were randomly selected for the study. Data for the study were obtained through the administration of a self-designed questionnaire to managers or accountants of the sampled firms through mail survey. Regression and t-test were used to test the hypotheses postulated for the study. The study showed that application of management accounting tools has a positive relationship with financial performance of companies’ survey. The study also found a significant difference in effectiveness of decision making between application of management accounting tools and traditional management accounting techniques and concludes that implementation of strategic management accounting practice is necessary to enhance organizational performance of the firm. The study therefore recommends that manufacturing companies, especially the ones listed and still tradable under NEPSE, put in place appropriate measures to apply modern management accounting tools called strategic management accounting practices to ensure efficient and realistic decision-making process that will enhance financial performance.